2016
DOI: 10.4103/0019-5154.190105
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and immunomodulatory effects of antibiotics and their use in dermatology

Abstract: Antibiotics (antibacterial, antiviral, and antiparasitic) are class of drugs which result in either killing or inhibiting growth and multiplication of infectious organisms. Antibiotics are commonly prescribed by all specialties for treatment of infections. However, antibiotics have hitherto immunomodulatory and anti-inflammatory properties and can be exploited for various noninfectious dermatoses. Dermatologists routinely prescribe antibiotics in treatment of various noninfectious disorders. This study will re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 133 publications
0
20
0
Order By: Relevance
“…Some authors advocate that they act by eradicating H. pylori , whereas others highlight a non-specific direct benefit from the use of antibiotics as the cause of clinical improvement. The confusion is further enhanced by the fact that some of the antibiotics known for their anti-inflammatory properties in rosacea, such as tetracyclines, metronidazole or macrolides, 67 are also used to treat H. pylori infection. 68 Moreover, different studies have used different statistical methods which could constitute a further explanation for the controversial conclusions, taking also into account that much evidence is derived from case series with a small number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate that they act by eradicating H. pylori , whereas others highlight a non-specific direct benefit from the use of antibiotics as the cause of clinical improvement. The confusion is further enhanced by the fact that some of the antibiotics known for their anti-inflammatory properties in rosacea, such as tetracyclines, metronidazole or macrolides, 67 are also used to treat H. pylori infection. 68 Moreover, different studies have used different statistical methods which could constitute a further explanation for the controversial conclusions, taking also into account that much evidence is derived from case series with a small number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential rationales for the use of clindamycin in COVID-19 patients can be attributed to its anti-inflammatory and immunomodulatory effects. Clindamycin was reported to modulate cytokine production in lipopolysaccharide-stimulated macrophages, to decrease TNF-α and IL-1β, to suppress the chemotaxis of polymorphonuclear leukocytes, to reduce inflammation, and to enhance the uptake of microorganisms by the host phagocytic cells [ 137 ]. It is also possible that it is being tested for antibacterial coverage in hospitalized patients with COVID-19-related pneumonia.…”
Section: Potential Small Molecule Inhibitors Of Early Viral Eventsmentioning
confidence: 99%
“…Several antibiotics, including minocycline and macrolides, present with both antimicrobial and anti-inflammatory properties as they de-escalate NLRP3 (Pradhan et al, 2016). Recent studies have shown that minocycline also presents with senolytic properties as aside from inhibiting NLRP3, it facilitates senescent cell removal (Labro, 2002; Li J. et al, 2016; Lee et al, 2017).…”
Section: Beta Amyloid: Friend or Foe?mentioning
confidence: 99%